Novel Frontiers of Treatment for Advanced Gastric or Gastroesophageal Junction Cancer (GC/GEJC): Will Immunotherapy Be a Future Direction? - Bai, Rilan; Chen, Naifei; Liang, Tingting; Li, Lingyu; Lv, Zheng; Lv, Xiaomin; Cui, Jiuwei (Frontiers in Oncology, 2020)
Considering the limited progress of chemotherapy and targeted therapy in improving the generally disappointing outcomes of advanced GC/GEJC, immunotherapies have been gradually developed and advanced into novel frontiers of treatment for advanced GC/GEJC. Nevertheless, the response to immunotherapy was not always satisfactory, and the emergence of resistance was unavoidable. These factors prompt the development of different combination therapies and predictive and prognostic biomarkers of efficacy to improve the outcomes of patients with advanced GC/GEJC, and to overcome drug resistance. This article discusses the advances of immune monotherapy, multiple current and ongoing clinical trials of immune combination therapy, immune-related adverse events, and various biomarkers in GC/GEJC.